Delincuencia organizada en el ordenamiento jurídico ecuatoriano - Palacios Gilces, Karol Evelyn (2022)
This research work entitled "Organized crime in the Ecuadorian legal system", is aimed at obtaining the Master's Degree in Procedural Law, it is concerned about the fact that, in the world order, organized crime is a phenomenon that occurs frequently, constantly and through different forms. Therefore, the different criminal organizations are developing certain criminal profiles that have as a common denominator, social dangerousness, and all its negative impacts. By virtue of the number of International Instruments issued and aimed at confronting organized crime, the laws worldwide have adapted their internal regulations to said treaties with the aim of correctly conceptualizing, characterizing and defining organized crime and its manifestations. Part of this is to adapt internal criminal regulations to said positions in a way that is understandable, clear and respectful of the technique of criminal law. It was drawn as a scientific problem: ¿If the criminal types of Organized Crime and Illicit Association, existing in the Ecuadorian criminal legal system to combat organized crime in Ecuador, should have decreased the rates of this phenomenon that exist today?, and, as a general objective: Analyze the legal configuration of the criminal types provided for in articles 369 and 370 of the COIP.........